Emergency Response Workshop on Fire Prevention and Control Using Fire Blankets and Fire Extinguishers - Nugroho, Budi Sulistiyo; Annasit; Nurrahman, Arif; Dharmawan, Aditya; Setiyono, Agus; Hamid, Farid Alfalaki; Handoko, Susilo; Widiyanto, Totok; Dewi, Astrie Kusuma; Indriani, Erdila (Civitas : Jurnal Pengabdian Masyarakat, 2025)
Fire incidents continue to increase in various regions in Indonesia due to low public awareness of prevention and early response measures. This community service activity aims to improve students' knowledge, skills, and preparedness in using fire blankets and portable fire extinguishers through experience-based training. The implementation methods include interactive lectures, live demonstrations, and controlled firefighting simulations. Pre- and post-training evaluations were used to measure changes in knowledge, skills, and safety attitudes. A total of 180 participants (aged 15–18 years) attended the training and completed the entire evaluation series. The results showed an average increase in knowledge scores from 52.3 to 86.8 points (+66%). Practical competence increased from 14% to 81% of participants who were assessed as being able to use the tools correctly. Attitudes and confidence in emergency response also showed significant improvement, from a score of 2.4 to 4.1 on the Likert scale. Qualitative feedback confirmed that participants felt better prepared to deal with small fires and had a better understanding of the importance of a safety culture in the school environment. These findings indicate that practice-based training is effective in strengthening fire preparedness among secondary school-aged groups. This workshop model offers an educational approach that can be replicated by other educational institutions as a risk mitigation strategy and to strengthen community-based safety culture.